Human papillomavirus-associated oropharyngeal carcinoma: trends in epidemiology and methods for detecting the virus in tumors - A. I. Stukan'; O. Yu. Chukhray; V. A. Porkhanov; R. A. Murashko; V. N. Bodnya; Yu. M. Makarova (Опухоли головы и шеи, 2018)
Oropharyngeal squamous cell carcinoma has been traditionally associated with tobacco and alcohol consumption. Nevertheless, latter 30 years have shown squamous cell carcinoma (OPSCC) incidence stagnation and increasing, despite the decrease in smoking prevalence. The incidence was recognized among white men of middle age, often non-smokers or former smokers in the investigations with smoking cessation data. It differs from traditional patient with OPSCC, older men, heavy smoker or alcohol drinker. The incidence of OPSCC is increased due human papilloma virus (HPV) infection. The infection transition is associated with sex and oro-genital contact may lead to HPV-infection of oropharynx and oral cavity. There are multiple types of HPV, but the majority of OPSCC is associated with HPV 16 type. Epidemiology of HPV-associated OPSCC, HPV-infection of oral cavity and/or oropharynx and HPV detection are discussed in the review.